Policy Implementation The Ministry Female Empowerment and Child Protection in the Prevention Sexual Violence against Women - Suprobowati, Dewi; Sugiharto, Mulus; Maulida Ikmal, Novita (KnE Social Sciences, 2023)
Sexual violence is often associated with the concept of community morality which is still a problem, both in the private sphere and in the public sphere. This research discusses abaout policy implementation of prevention sexual violence against women, as well as the implications of sexual violence for gender studies in Indonesia. The spesific targers of this research are the policies implementated by The Ministry Female Empowerment and Child Protection regarding cases of sexual violence and obstacles in achieving these policies. Than how the process and progress. In addition, it also produces policy recomendations formulated in the form of a policy paper on the prevention of sexual violence, especially against women. This reseach method uses descriptive qualitative methods that is library research. The Ministry Female Empowerment and Child Protection preventive efforts are to form programs and policies, where the community can change their mindset about the existence of a patriarchal culture. In accordance with gender studies in Indonesia that sexual violence is a form of gender based violence, so there is a need for efforts to handling with the problem of sexual violence. With the cooperation of various parties including the goverment and police, it is hoped that the high rate of sexual violence can be minimixed. Keywords: Sexual violence; community morality; policy implementation; gender studies